ILLOCUTIONARY ACTS FOR DIFFERENT RACES IN DR. KING’S UTTERANC S OF AVA DUVERNAY’S SELMA MOVIE - Meryka Provitasari; Dwi Setiyadi; Lusia Kristiasih Dwi Purnomosasi (English Teaching Journal : A Journal of English Literature, Language and Education, 2016)
This research aims to find out the racism occurs from verbal language by using Selma movie as the object. It is based on insight from Yule’s (1996) illocutionary act theory to analyze the type of Martin Lurther King’s utterances and Hymes’ (in Wardhaugh, 2006) speaking ethnography theory to analyze the context behind Martin Lurther King’s utterances. The writer finds commissive act (8%); expressive act (44%); and directive act (48%) as the illocutionary act which be used by King, and some datum of speaking ethnography without genre because genre can be found in written text only. The writer finds unity, solidarity, nationality and movement as the meanings which be categorized into racism’s representation from analysing the type and context.